A morphological investigation of marine transgression in estuaries. Issue 3 (11th January 2021) - Townend, Ian; Zhou, Zeng; Guo, Leicheng; Coco, Giovanni
Abstract: The landscape setting of estuaries varies widely and is an important aspect of determining how they evolve. This paper focusses on alluvial estuaries in river valleys and how they respond to sea level rise. We examine the implications of marine transgression, as a response to sea level rise, where the estuary moves upwards and landwards to maintain its position in the tidal frame (so‐called stratigraphic rollover). Here we encapsulate such kinematic movement of the estuary morphology using a 'morphokinematic' model, to assess the potential response to sea level rise and sediment supply. The model of the estuary form includes a single convergent channel, intertidal and surrounding floodplains (the valley) and allows the relative importance of the space available for deposition of sediments, the accommodation space, to be investigated as a function of rates of sea level rise and sediment supply. The transgression of the system is determined using a sediment mass balance, taking account of any supply from the river and marine environment. Model results confirm that the transgression distance, measured as the distance the entity moves landward, varies in proportion to the change in accommodation space, which mainly depends on the floodplain area. As the size of the floodplain reduces, the transgression distance is less and the system becomes much more sensitive to changes in the rate of sea level rise or changes in sediment supply. The greater demand for sediment when a floodplain is present results in greater cannibalization of the estuary form (i.e. greater landward movement) to meet the sediment demand. When the floodplain is disconnected from the estuary, the synergistic relationship is lost and the accommodation space increases. The capacity for restoration will depend on the availability of sediment and the prevailing rate of sea level rise. Abstract : An estuary can maintain its form relative to rising sea level by translating landwards. The transgression distance is dependent on the sediment demand to fill the accommodation space in the surrounding valley and is sensitive to the rate of sea level rise and sediment availability. Exclusion of floodplains, by flood defences, may create a 'coiled spring' effect, which when released, as defences fail or are removed, will create an increase in accommodation space and the potential for estuary transgression.